Bibliometric Analysis of Research Trends in Digital Learning Media for Technical and Vocational Education and Training (TVET) - Roni Arya Gunawan; Agung Rorhi Prayudha; Purwandari Nur Tristianigsih (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2026)
This study aims to map the trends, research focus, and developmental dynamics of studies on digital learning media in technical and vocational education during the period 2016–2026. The study employed a bibliometric analysis approach conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, with data mining carried out using the Dimensions database. The analysis was performed using VOSviewer software to identify research trends, keyword relationships, and patterns of author collaboration. The results indicate that the number of publications fluctuated but showed an overall upward trend, with a significant increase after 2021 and reaching a peak in 2025. Based on network visualization and overlay visualization results, research on digital learning media in technical and vocational education demonstrates an interconnected thematic structure that evolves dynamically. The keyword “vocational education and training” serves as a central node integrating various topics, such as learning and learning outcomes, the use of multimedia and technology, the development of media based on the ADDIE model, the utilization of virtual laboratories, and the implementation of immersive technologies such as augmented reality. Over time, the research focus has shifted from online learning and conventional multimedia toward more advanced digital technologies grounded in cognitive theory, such as cognitive load theory, android-based courseware, and the strengthening of 21st-century skills relevant to industry needs. Overall, the findings indicate substantial research opportunities related to the integration of artificial intelligence (AI) in digital learning media within the field of technical and vocational education, and this topic is recommended as a direction for future research